Silenced victims of wartime sexual violence - Simić, Olivera (Post-conflict law and justice, 2018)
Conflict-related sexual violence and its "silences" -- Revisiting mass rape in Bosnia and Herzegovina -- Ethnic politicisation of conflict-related sexual violence -- Becoming a victim in Bosnia and Herzegovina -- The women's court in Sarajevo : challenges and reflections -- The role of civil society in assisting women victims of conflict-related sexual violence -- The politics of writing/researching the "silenced" women